Analisis Dampak Mud Pumping Terhadap Kerusakan Sleeper Pada Jalur Kereta Api Tanjung Karang – Rejosari (Studi Kasus Divre IV Tanjung Karang) - Muhammad Rizki Arif; Roy Jones Lumban Siantar; Febriyadi Febriyadi; Arif Setyaji; Nurwanda Sari; Nur Annisa Mardhotillah; Nur Syahidah Aini; Rahmatika Dwi Putri Jori (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
This study analyzes the impact of mud pumping on track stability and damage to K-550-type monoblock concrete sleepers on the Tanjung Karang–Rejosari line (DIVRE IV Tanjung Karang). This Class I track, with a gauge of 1,067 mm, carries an annual load of 82,883.21 tons. Mud pumping causes water mixed with mud to rise to the surface of the ballast, which disrupts load distribution and the stability of the track structure. The research methodology comprises four main stages: (1) field observations at four critical locations (Km 13+8/9, Km 14+2/3, Km 25+2/3, and Km 28+5/6); (2) measurements using a Dynamic Cone Penetrometer (DCP) and a densometer to obtain RC, CBR, and Evd parameters; (3) track geometry evaluation to detect elevation deviations; and (4) technical analysis of sleepers based on an elastic modulus of 150,093.30 kg/cm² and a permissible stress of 210 kg/cm². The research results indicate that the most critical condition is at Km 25+2/3, with an RC value of 14.37 kN/m, a CBR of 3.85%, and an Evd of 41.6 MN/m². Overall, several segments have CBR values below the safe threshold (15–24%), indicating a significant decrease in ballast density due to mud pumping. Technical analysis confirms that mud accumulation disrupts the distribution of effective stress and accelerates sleeper deterioration. As a mitigation measure, it is recommended to install woven geotextile, replace the ballast material, and implement periodic monitoring using DCP/densometer instruments to maintain track stability within acceptable limits and extend the service life of the railway infrastructure.